Unpacking Police Endorsement of Myths Surrounding Intimate Partner Violence Against Women: Formation and Implications - Nørgaard Madsen, Linda (Violence against women, 2024)
Drawing on a qualitative case study consisting of interviews with Danish police trainees, patrol officers, and police detectives, this article explores police endorsement of myths surrounding male-perpetrated intimate partner violence against women (IPVAW) and its influence on police response to IPVAW incidents. The findings show that police officers begin to believe in the myths to cope with negative emotions arising from repeated exposure to IPVAW victims, who do not behave according to expected norms of being cooperative, responsible, and innocent. This makes police officers meet victims with skepticism, low spirit, and hopelessness, making them refrain from initiating further criminal investigations, opening criminal cases, and pursuing arrests.